Monitoring the Resolution of Acute Exacerbation of Airway Bronchoconstriction in an Asthma Attack Using Capnogram Waveforms. (18th April 2023) - Shikama, Mio; Yamamoto, Miyuki; Osawa, Itsuki; Sato, Takuya; Hirayama, Ichiro; Hayase, Naoki; Matsubara, Takehiro; Doi, Kent
Abstract : BACKGROUND: Patients with acute bronchospasm can show a distinct slope of the capnogram ("shark fin") as a result of asynchronous alveolar excretion. Although the slope of the upward alveolar plateau (phase III) in the capnogram waveforms of non-intubated patients is known to help monitor the therapeutic response to acute bronchospasm, little is known about the significance of its slope among intubated patients. Therefore, we quantified the phase III slope of an intubated patient with acute asthma to investigate whether capnogram waveforms could be useful for identifying the response to antibronchospasm treatment in real time. CASE SUMMARY: The patient was a 53-year-old man who had a history of asthma. He presented to the emergency department with the primary complaint of respiratory distress. He was diagnosed with severe asthma attack and required invasive mechanical ventilation for 10 days, during which we quantified the phase III slope of the capnogram. The phase III slope decreased during treatment, with a significant reduction from the third to the fourth day; however, a significant decrease in end-tidal carbon dioxide (EtCO 2 ) was observed from the fifth to the sixth day. We found that the slope values decreased earlier than EtCO 2 reduction, although the absolute EtCO 2 values eventually decreased in response to antibronchospasm treatment. CONCLUSION: There were several reports that evaluated the phase III slope in non-intubated patients with asthma, but this is the first report measuring the phase III slope in an intubated patient over several days. Capnogram waveforms may serve as useful real-time indicators to monitor acute bronchospasm among mechanically ventilated patients.